Pengaruh Kepatuhan Syariah, Literasi Keuangan, dan Persepsi terhadap Lembaga Zakat terhadap Kesejahteraan Ekonomi Mustahik Peran Mediasi Kepercayaan terhadap Lembaga Keuangan Syariah - Muhammad Alif Shafwan Hanif Sanjaya (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of sharia compliance, Islamic financial literacy, and perceptions of zakat institutions on the economic welfare of zakat recipients (mustahik), with trust in Islamic financial institutions as a mediating variable. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), the study collected data from 114 mustahik residing in the Greater Jakarta area who had received productive zakat assistance for at least six months. The results indicate that sharia compliance and perceptions of zakat institutions have a significant direct effect on trust in Islamic financial institutions, while Islamic financial literacy does not. Furthermore, only perceptions of zakat institutions show a significant direct effect on mustahik's economic welfare. Trust in Islamic financial institutions does not serve as a significant mediating variable in this model. These findings highlight the importance of strengthening public perceptions of zakat institutions to enhance the economic welfare of beneficiaries and suggest that trust mechanisms alone may not suffice to drive welfare improvements without direct institutional support.